THE EFFECT OF CEO2 NANOPARTICLE ADDITION ON PCL/CENTELLA ASIATICA NANOFIBER AS A MEMBRANE FOR HEALING DISCOID LUPUS ERYTHEMATOSUS WOUNDS - R M Sihombing, Jackson
Optical fiber consists of three components, core, cladding, and coating. Polymer fiber-based optical fiber core components are usually made from polymethyl methacrylate (PMMA). However, PMMA cannot be used in special applications that require temperature resistance above 100°C. In special applications, high performance fibers are usually required. Polycarbonate (PC) has almost the same optical properties as PMMA, but with higher heat resistance so that PC can be an alternative material for optical fibers. The tensile strength of PC fiber based on references is known to be 119 MPa. For high performance fibers, the tensile strength of these PC fibers needs to be increased. In this research, PC fiber was made using the extrusion method at temperatures of 210 °C, 220 °C and 230 °C, then continued with drawing treatment. This research aims to analyze the optimal fiber manufacturing process to obtain PC fiber with high strength. In the research results, it was observed that increasing the extrusion temperature to 230 °C influence on reducing the tensile strength of PC fiber to 123 MPa. The drawing treatment carried out was proven to increase the tensile strength of PC fibers by up to 133%. In this study, light absorbance by PC fibers was also observed. The research results observed that the relative light absorbance decreased with increasing extrusion temperature.